2010
DOI: 10.2298/sarh1010570m
|View full text |Cite
|
Sign up to set email alerts
|

Trends of risk factors in coronary surgery

Abstract: The number of CABG increases despite the enlargement of PCI. The risk for isolated CABG given by EuroSCORE increases over years. The risk factors, significantly contributing to higher EuroSCORE are: older age, extracardiac arteriopathy, recent myocardial infarction and emergency operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
7
1
2
Order By: Relevance
“…The EuroSCORE II is a reflection of continuous improvement in everyday clinical practice and mainly poses a recalibration aimed at replicating today's outcomes in cardiac surgery. In our two previous articles, 23,24 we reported on the constant improvement of the service provided in our hospital with the coronary surgery mortality of 2.7% in 2001, and the mortality of 1.5% in 2008. These results were achieved despite the trend of constant increase in the number of average risk factors present as well as the increase in the average EuroSCORE.…”
Section: Discussionmentioning
confidence: 81%
“…The EuroSCORE II is a reflection of continuous improvement in everyday clinical practice and mainly poses a recalibration aimed at replicating today's outcomes in cardiac surgery. In our two previous articles, 23,24 we reported on the constant improvement of the service provided in our hospital with the coronary surgery mortality of 2.7% in 2001, and the mortality of 1.5% in 2008. These results were achieved despite the trend of constant increase in the number of average risk factors present as well as the increase in the average EuroSCORE.…”
Section: Discussionmentioning
confidence: 81%
“…Based on the EuroSCORE model the BMI appears not to be considered as a potential risk factor 33,34 . The STS scoring system includes low BSA as an independent risk factor (OR 0.91 per 1 unit).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies [8][9][10][11], we analyzed the predictive value of the EuroSCORE model in coronary surgery, as well as trends of risk factors included in the EuroSCORE model. It was observed that the profile of coronary patients undergoing surgery in one of the cardiac surgery centres is drastically changing primarily due to the significantly advanced percutaneous techniques for myocardial revascularization.…”
Section: Discussionmentioning
confidence: 99%